Comparison of maximal lactate steady state with V2, V4, individual anaerobic threshold and lactate minimum speed in horses - Soares, O.a.b. [UNESP] (2014)
The anaerobic threshold is a physiologic event studied in various species. There are various methods for its assessment, recognized in the human and equine exercise physiology literature, several of these involving the relationship between blood lactate concentration (LAC) and exercise load, measured in a standardized exercise test. The aim of this study was to compare four of these methods: V2, V4, individual anaerobic threshold (IAT) and lactate minimum speed (LMS) with the method recognized as the gold standard for the assessment of anaerobic threshold, maximal lactate steady-state (MLSS). The five tests were carried out in thirteen trained Arabian horses, in which velocities and associated LAC could be measured. The mean velocities and the LAC associated with the anaerobic threshold for the five methods were respectively: V2 = 9.67±0.54; V4 = 10.98±0.47; V IAT = 9.81±0.72; V LMS = 7.50±0.57 and V MLSS = 6.14±0.45m.s-1 and LAC IAT = 2.17±0.93; LAC LMS = 1.17±0.62 and LAC MLSS = 0.84±0.21mmol.L-1. None of the velocities were statistically equivalent to V MLSS (P<0.05). V2, V4 and V LMS showed a good correlation with V MLSS , respectively: r = 0.74; r = 0.78 and r = 0.83, and V IAT did not significantly correlate with V MLSS. Concordance between the protocols was relatively poor, i.e., 3.28±1.00, 4.84±0.30 and 1.43±0.32m.s-1 in terms of bias and 95% agreement limits for V2, V4 and LMS methods when compared to MLSS. Only LAC LMS did not differ statistically from LAC MLSS. Various authors have reported the possibility of the assessment of anaerobic threshold using rapid protocols such as V4 and LMS for humans and horses. This study corroborates the use of these tests, but reveals that adjustments in the protocols are necessary to obtain a better concordance between the tests and the MLSS.